Light Absorption Properties and Electronic Band Structures of Lead‐Vanadium Oxyhalide Apatites Pb5(VO4)3X (X=F, Cl, Br, I). Issue 4 (23rd January 2020) - Nakamura, Masashi; Oqmhula, Kenji; Utimula, Keishu; Eguchi, Miharu; Oka, Kengo; Hongo, Kenta; Maezono, Ryo; Maeda, Kazuhiko
Abstract: The Pb‐V oxyhalide apatite compounds Pb5 (VO4 )3 X (X=F, Cl, Br, I) were successfully synthesized using a facile solution method and studied with respect to their structural/optical characteristics and electronic band structures. UV‐visible diffuse reflectance spectroscopy, electrochemical analysis and first‐principles calculations showed that the synthesized apatites behaved as n‐type semiconductors, with absorption bands in the UV‐visible region that could be assigned to electron transitions from the valence band to a conduction band formed by hybridized V 3d and Pb 6p orbitals. Among the apatites examined, Pb5 (VO4 )3 I had the smallest band gap of 2.7 eV, due to an obvious contribution of I 5p orbitals to the valence band maximum. Based on its visible light absorption capability, Pb5 (VO4 )3 I generated a continuous anodic photocurrent under visible light ( λ >420 nm) in a solution of 0.1 m NaI in acetonitrile. Abstract : The optical properties and electronic band structures of the oxyhalide apatites Pb5 (VO4 )3 X (X=F, Cl, Br, I) were studied. Among these, Pb5 (VO4 )3 I had the smallest band gap because I 5p orbitals having a higher energy level than O 2p orbitals constituted the valence band maximum. This property enabled conversion of visible light to electricity.